A Polysaccharide Purified From Ganoderma lucidum Acts as a Potent Mucosal Adjuvant That Promotes Protective Immunity Against the Lethal Challenge With Enterovirus A71 - Lin, Yu-Li; Shih, Chiaho; Cheng, Pei-Yun; Chin, Chiao-Li; Liou, An-Ting; Lee, Po-Yi; Chiang, Bor-Luen (Frontiers in Immunology, 2020)
Enterovirus A71 (EV-A71), the pathogen responsible for the seasonal hand-foot-and-mouth epidemics, can cause significant mortality in infants and young children. The vaccine against EV-A71 could potentially prevent virus-induced neurological complications and mortalities occurring due to the high risk of poliomyelitis-like paralysis and fatal encephalitis. It is known that polysaccharide purified from Ganoderma lucidum (PS-G) can effectively modulate immune function. Here, we used PS-G as an adjuvant with the EV-A71 mucosal vaccine and studied its effects. Our data showed that PS-G-adjuvanted EV-A71 generated significantly better IgA and IgG in the serum, saliva, nasal wash, bronchoalveolar lavage fluid (BALF), and feces. More importantly, these antibodies could neutralize the infectivity of EV-A71 (C2 genotype) and cross-neutralize the B4, B5, and C4 genotypes of EV-A71. In addition, more EV-A71-specific IgA- and IgG- secreting cells were observed with the used of a combination of EV-A71 and PS-G. Furthermore, T-cell proliferative responses and IFN-γ and IL-17 secretions levels were notably increased in splenocytes when the EV-A71 vaccine contained PS-G. We also found that levels of IFN-γ and IL-17 released in Peyer's patch cells were significantly increased in EV-A71, after it was combined with PS-G. We further demonstrated that both CD4+ and CD8+ T cells were able to generate IFN-γ and IL-17 in the spleen. An easy-accessed model of hybrid hSCARB2+/+/stat‐1‐/‐ mice was used for EV-A71 infection and pathogenesis. We infected the mouse model with EV‐A71, which was premixed with mouse sera immunized with the EV-A71 vaccine with or without PS-G. Indeed, in the EV-A71+PS-G group, the levels of VP1-specific RNA sequences in the brain, spinal cord, and muscle decreased significantly. Finally, hSCARB2-Tg mice immunized via the intranasal route with the PS-G-adjuvanted EV-A71 vaccine resisted a subsequent lethal oral EV-A71 challenge. Taken together, these results demonstrated that PS-G could potentially be used as an adjuvant for the EV-A71 mucosal vaccine.